A model of ice friction for a speed skate blade - Lozowski, E.; Szilder, K.; Maw, S. (Sports Engineering, 2013)
The FAST 2.0i numerical model of ice friction was developed for an inclined speed skate blade. It describes ice friction at sliding velocities sufficiently high to produce a lubricating layer of meltwater, which completely separates the ice and slider surfaces (known as the hydrodynamic friction regime). Friction arises from ploughing a groove in the ice and from the shear stress in the lubricating Couette flow. The model takes into account frictional melting, heat conduction into the ice and the lateral squeeze flow of the lubricating liquid. We use the numerical model to calculate the ice-blade contacts, the parameters of the lubricating liquid layer, and the relative importance of the various contributions to the overall friction coefficient. We also use it to perform sensitivity studies and to predict the variation of ice friction during a typical skating stroke. The model results compare favorably with measurements of the ice friction coefficient during speed skating, made by others.